The Influence of Multicultural Education and Learning Motivation on Student Academic Achievement - Labuan, Bernadina Waha; Pangemanan, Stefhanus Hanny (Journal La Edusci, 2025)
This study aims to determine the extent of influence of multicultural education and student motivation on student academic achievement at St. Familia Catholic Vocational School. The method used in this study is a quantitative research method using a correlative approach with the aim of testing the hypothesis regarding the magnitude of the influence and whether or not there is a relationship between the independent variables (X1 and X2) and the dependent variable (Y). The sample in this study according to the Slovin formula was 62 people. The research instrument used was distributing questionnaires with alternative answers in the form of statements provided. Before conducting data analysis, analysis requirements were first tested, namely the normality test, linearity test and multicollinearity test. Hypothesis testing used multiple Linear Regression analysis. The results of the study showed that multiculturalism education partially influenced student academic achievement at Santa Falimia Tomohon Vocational School with a percentage of 81.9% and was in the very good category. Learning motivation partially influenced student academic achievement at Santa Falimia Tomohon Vocational School with a percentage of 54.3% and was in the good category. Multicultural education and learning motivation together influence students' academic achievement at Santa Falimia Tomohon Vocational School with an influence percentage of 91.7% and is in the very good category.